Priority reef areas in the pacific coast of the Philippines for Marine Protected Area deployment - Licuanan, Wilfredo Y. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2011)
The present paper seeks to provide a scientific basis for the establishment of marine protected areas (MPA) through an integrated and objective analysis of biodiversity survey data, which permits ranking of various sites in order of their importance as potential MPA. The approach proposed here involves the determination of biodiversity values for each of the four taxonomic groups (corals, reef fishes, seagrasses and seaweeds) and an assessment of the levels of risk for each of the survey sites to human degradation and natural disturbance. The biodiversity and risk scores were then combined into one MPA priority score using a conversion table. Five of the 17 geographic units (mostly small islands) stand out as high priority sites for conservation: Biri in Northern Samar; Ticao and Palaguigue Islands in Masbate; Pujada Bay, Davao Oriental; Homonhon and Suluan Islands, Eastern Samar; and Laoang, Northern Samar. The approach described here provides a framework by which an objective, repeatable prioritization of conservation value of various areas could be undertaken. Although the final measures are not absolute, it allows one to make explicit the assumptions made about the characters and measures used in prioritization and assign relative weights to various species, taxonomic groups and data sets, thereby reducing the impact of an observer's subjectivity.